Developing a Holistic Framework for Assessing the Development of the Digital Economy: A Systematic Review of Key Dimensions and Indicators - Zhong, Ni; Cheng, Ming Yu; Tey, Sheik Kyin; Fok, Kuk Fai (Journal of Telecommunications and the Digital Economy, 2024)
Rapid advancements in information and communication technologies (ICT) have accelerated the expansion of the digital economy (DE). However, the lack of a universally accepted definition has hindered a systematic assessment of the progress of the DE. A robust framework to evaluate various aspects of DE activities is crucial to fully capture the potential of the DE. This study conducts a systematic review of academic literature to identify and analyse various dimensions of the DE, aiming to propose a framework to assess the development of the DE. A comprehensive analysis of 161 articles from the Scopus database (2010–2024) identifies four core dimensions, namely digital infrastructure, digital industrialisation, industrial digitisation and digital innovation as the primary focus of existing DE research. These findings lay the groundwork for developing the framework to assess the development of the DE.